PENYULUHAN TENTANG KULIT BATANG SALAM SEBAGAI OBAT ANTIDIARE DI PUSKESMAS PATUMBAK - Bunga Rimta Barus; Delisma Marsauli Simorangkir; Linta Meliala; Anggun Syahfitri (Jurnal Pengabdian Masyarakat Putri Hijau, 2022)
Counseling on the efficacy of the bark of salam which aims to provide benefits about healing diarrhea at the Patumbak Public Health Center in one of the Deli Serdang districts aimed at children aged 6-17 years, by applying promotive and preventive nature through planning, mobilization, implementation, monitoring , control and appraisal. Counseling on the efficacy of the bark of salam at the Public Health Center of Patumbak, Deli Serdang Regency is aimed at increasing understanding to children aged 6-17 years, as well as parents who accompany their children, so that they can identify the symptoms of diarrhea, so that it can prevent or treat it, and malaise. - children and their parents can know the importance of monitoring their children's diet, which is healthy, which parents must take care of. Counseling will be carried out in a lecture style with conditions with discussion and brain storming that stimulates the counseling atmosphere. The evaluation of the activities was assessed from the support of the Patumbak Health Center, the timeliness of implementation, the facilities used, the number of participants who attended the counseling and the participation of the participants. Counseling participants were invited to express opinions, especially the problems faced at the Patumbak Health Center regarding anti-diarrhea so that solutions could be sought together. The results obtained from children and their parents after receiving counseling can understand well the benefits of counseling from the Patumbak Public Health Center regarding the use of the benefits of bay bark for healing. knowledge of the importance of health for their children, Families are willing to provide education and enthusiasm about the importance of the benefits of using bay bark, Parents of children and children aged 6-17 years after receiving counseling can understand well the benefits of counseling from the Patumbak Public Health Center regarding the utilization of the efficacy of the bark of salam for antidiarrheal disease in children aged 6-17 years, which has been described in their minds as just eating delicious food but not necessarily healthy for the body for all children. However, after following the counseling, children – children aged 6-17 years d can understand more fully the benefits of counseling. Community Health Center cadres, who have been providing services to children only in moderation, can change well by providing innovative promotions.